GAMBARAN DAMPAK PANDEMI COVID-19 TERHADAP DESTINASI DAN PARIWISATA DI INDONESIA - Andin Rusmini (Kepariwisataan: Jurnal Ilmiah, 2021)
Indonesia was shocked by the entry of the Covid-19 virus that was sweeping the world. The virus, which first occurred in the Chinese city of Wuhan, occurred in early 2020, was so massive and caused many deaths. The calamity of the entry of the Covid-19 virus also coincided with many other natural events that occurred in Indonesia. Starting from the tsunami disaster in Palu, the earthquake in Lombok, landslides and flash floods in West Java, Sumatra and not to mention DKI Jakarta, the handling to prevent the transmission of the corona virus has not been able to run optimally. However, due to the increasingly dangerous corona virus, the government finally created a Task Force for handling the Corona Virus. Destinations in Indonesia have not been spared from the Covid-19 outbreak, as well as tourism in Indonesia, which has been closed for an indefinite period of time. In fact, many tourism businesses eventually went bankrupt and went out of business. That's why this normative research was carried out by the author, to find out how the impact of the Covid-19 pandemic that occurred in Indonesia.Keywords: Covid-19, Destinations, Tourism